A comparative optimization of a trigeneration system with an innovative integration of solar Heliostat towers and Hydrogen production unit. (October 2021) - Izadi, Ali; Ahmadi, Pouria; Bashiri Mousavi, Shadi; Fakhari, Iman
Graphical abstract: Abstract: This research deals with a study of the improvement of a gas turbine-based power plant with solar heliostat towers and thermoelectric generators to enhance its performance. The proposed configuration consists of a solar-boosted gas turbine as a prime mover equipped with a Rankine and organic Rankine cycle (ORC), a single flash desalinated unit, a single effect LiBr/H2 O absorption chiller, and thermoelectric generators. The study illustrates that preheating inlet air leads to a decrease in the amount of CO2 and CO, but it increases the amount of NO. The effect of introducing the thermoelectric generator is also assessed on the performance criteria of the system through a parametric study. The effect of major decision variables on total exergy destruction rate, exergy efficiency of the system, total work, emissions, cooling load and desalinated water mass flow rate are investigated. The main novelty of this research is the comparative optimization of the proposed system to investigate the effect of the solar boosted combustion chamber and thermoelectric generators. Multi-objective optimization is also applied considering some reasonable constraints on the system to optimize the total cost and exergy efficiency of the system simultaneously. The results show that using solar energy can reduce fuel consumption from 0.371 kg/s to 0.1839 kg/s and is also has a positive effect on the exergy efficiency of the system, and the exergy efficiency increases by 2.92%. Using standard TEG TGM199-1.4–2.0 also increases the total power generated increases by 17.8 kW, and total exergy increases by 0.265. this system is also able to produce 1.6184 kg/s freshwater and a 748.08 kW cooling load.